Development of ulvan‐based emulsions containing flavour and fragrances for food and cosmetic applications. (24th July 2019) - Morelli, Andrea; Massironi, Alessio; Puppi, Dario; Creti, Donato; Domingo Martinez, Elia; Bonistalli, Camilla; Fabroni, Cosimo; Morgenni, Fabrizio; Chiellini, Federica
Abstract: In the present work, ulvan, a sulphated polysaccharide of algal origin, was innovatively investigated as stabilizing and emulsifying agent in colloidal formulations containing functional agents for food and cosmetic applications in virtue of its edibility and amphiphilic character. Ulvan was successfully submitted to chemical modification with biocompatible fatty acid moieties to increase the amphiphilic properties of the polysaccharide without compromising its safety profile. Oil in water (O/W) emulsions were developed using the ultrasonication method as an easy and rapid homogenization process. The stability of the obtained formulations was assessed by visual inspection, size distribution and zeta potential analysis. Stable emulsions were obtained by using either native or chemically modified polysaccharide. The most promising formulations based on the use of native ulvan were successfully implemented as clouding and flavouring agents in soft drink beverages and as stabilizing and perfuming agents in body cream milk products. The obtained results may open new perspectives on the exploitation of abundant waste biomasses as sources of biocompatible high value added materials suitable for being applied in critical applications as a safe alternative to synthetic chemicals. In particular ulvan could represent a valuable platform of functional and bioactive compounds with promising properties as stabilizing and emulsifying agents for food and cosmetic applications. Abstract : Ulvan, a sulphated polysaccharide of algal origin, was successfully used as novel emulsifying and stabilizing agent of microstructured colloidal formulations for food and cosmetic applications. Results indicate the possibility of exploiting waste algal biomass as source of biocompatible and functional materials for food and cosmetic products.